Ответы и объяснения

  • lena85
  • почетный грамотей
2014-03-26T14:03:03+04:00
2) 4(a² - 3a + 1) = 4a² - 12a + 4  (Б)
3) -ab(5a - 8b²) = -5a²b + 8ab² (Г)
4) -6a + ab -(-8ab + a) = -6a + ab + 8ab - a = -7a + 9ab (Г)
5) (3a + 1) ( a -1) = 3a² - 3a + a - 1 = 3a² - 2a -1 (В)

Лучший Ответ!
2014-03-26T14:10:15+04:00
1)3*4-7*2*1+4=12-14+4=2(б)
2)4а^2-12а+4 (б)
3)-5а^2в+8ав^3(г)
4)-6а+ав+8ав-а=-7а+9ав(г)
5)3а^2-3а+а-1=3а^2-2а-1(в)
6)2х^2+6х-2-2х^2-2х+2=0
4х=0
Х=0(а)
7)1)4ав^2-8а^3в=4ав^2-8а^3в (да)
2) 15х^8+3х^4+х=15х^8+3х^4(нет)(б)
спс
^ а это что
степень
степень
Спасибо вы мне помогли очень!)